Predictive ecotoxicological modeling of ionic liquids using QSAR techniques: A mini review - Rehman, A.U. (John Wiley and Sons Inc, 2022)
All living beings must be protected from the incessantly increasing environmental pollution caused by hazardous chemicals. This imposes a serious obligation on the biological, chemical, and pharmaceutical industries to develop less harmful chemicals. Regarding the hazardous and harmful prospects of such chemicals, various initiatives have been taken globally. The concept of âgreen chemistryâ is the most remarkable, which concentrates on the application of eco-friendly chemicals. Although ionic liquids (ILs) are new chemicals, thay have recently gained much prominence because of their great importance. Recent research shows that they have many different applications, ranging from the specific performance tasks to chemistry with minimal environmental impact, and have earned the designation of âgreen chemicals.â However, studies have shown that ILs are toxic chemicals and can display extreme levels of toxicity. Likewise, they pose a high danger of bioaccumulation because of their structural components. Also, ILs present waste generation and separation issues during their synthesis. Toxicity testing of ILs is a tedious and resource-intensive process. Improvements in and the use of quantitative structureâactivity relationships (QSARs) for an imaginative plan of safe-by-design ILs have, of late, turned into an exploration need. QSAR is a predictive model that establishes a noetic chance to discover the structural properties of ILs to different toxicological and physicochemical endpoints. The process selectivity of the new analogs leads to their environmental friendliness. A comprehensive review has been carried out to provide a concise account of different QSAR works carried out on these chemicals, as well as their related health, safety, and environmental issues, while also discussing the applicability of the philosophy of âgreen chemistry.â. Â© 2022 American Institute of Chemical Engineers.